KNOWLEDGE AND UTILISATION OF HIV/AIDS PREVENTION TECHNIQUES AMONG SEMI-SETTLED PASTORALISTS IN SOUTHWESTERN NIGERIA
The migratory pattern of Semi-Settled Pastoralists (SSP) encourages HIV/AIDS spread and as well limits access to sources of its information. Most studies on HIV/AIDS prevention have targeted settled individuals to the neglect of SSP; hence, information on extent of use of HIV/AIDS Prevention Techniques (HAPT) by SSP is scanty. Therefore, knowledge and utilisation of HIV/AIDS prevention techniques among the SSP in southwestern Nigeria, were investigated. Multi stage sampling technique was used to select respondents for the study. The Derived Savannah Areas (DSA) of Ogun and Oyo states were purposively selected due to high concentration of SSP in the area. Fifty percent of the Local Government Areas (LGAs) in the DSA and eight percent of SSP households from the LGAs were randomly chosen to give 94 households for Ogun and 236 for Oyo states. From each household, an available adult was chosen to elicit information. Structured interview schedule was used to collect the data on respondents' personal characteristics, sources of HIV information, knowledge, utilisation and Attitude Towards Utilisation (ATU) of HAPT. Data were analysed using descriptive statistics, composite indices, chi-square, t-test, Pearson product moment correlation and multiple regression analysis at p=0.05. Mean age of respondents was 38.0± 13.0 years, 91.8% were married and 100.0% were muslim while 90.0% could speak fulfulde fluently. Eighty percent of the respondents indicated radio as the major source of information on HAPT. Knowledge of HAPT was above mean value (14.0) for 60.6% in Ogun and 52.5% in Oyo. Utilisation of HAPT was above the mean value (7.6 ± 2.3) for 87.2% in Ogun and 41.5% in Oyo. The ATU of HAPT was favourable among 85.1% of respondents in Ogun compared to 45.8% in Oyo. Mean knowledge of HAPT in Ogun was 15.3 ± 2.0, while it was 13.5 ± 2.3 in Oyo. Mean utilisation of HAPT was 9.2 ± 1.4 in Ogun and 6.9 ± 2.3 in Oyo. Utilisation of HAPT was significantly related to level of education (?2= 30.11), knowledge (r = 0.26) and attitude (r = 0.66). Information sources that were significantly related to utilisation of HAPT were mosques (?2= 6.12), friends (?2= 7.22) and produce customers (?2= 7.07). There was significant difference (t = 10.449) in utilisation of HAPT among the respondents in Ogun and Oyo. Attitude (? = 0.16) and knowledge (? =1.12) determined utilisation of HAPT among SSP in Ogun, while number of years of stay in community (? = 3.66), attitude (? = 0.149) and knowledge (? = 0.889) were the significant predictors in Oyo. Years of stay in community (? = 0.036), level of education (? = 0.198) and attitude (? = 2.846) determined utilisation of HAPT across the states. Semi-settled pastoralists' utilisation of HIV/AIDS prevention techniques was generally high in Ogun than Oyo. Level of education, knowledge of HIV/AIDS prevention techniques and agents like mosques, friends and produce customers enhanced utilisation.